2019
DOI: 10.7759/cureus.5720
|View full text |Cite
|
Sign up to set email alerts
|

Complete Agenesis of Dorsal Wall of Sacral Canal: A Case Report

Abstract: The sacral canal is the continuation of the vertebral canal in the sacrum. The sacral canal contains spinal meninges, lumbar and sacral part of spinal nerves and filum terminale. So sacral canal has been used for the caudal epidural block. During routine osteology demonstration classes for undergraduate students, we observed a dry human sacrum with complete agenesis of the dorsal wall of the sacral canal. Knowledge of these variations is important to diagnose lower back pain, sciatica, caudal regression syndro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The total absence (agenesis) of the sacral canal of the dorsal wall among the Bangladeshi population was 5.0%. Multiple studies revealed that the incidence of complete agenesis of the dorsal wall in the sacrum varies from 2.58% to 20% (Table 2) [10,30,59,[62][63][64][65][66][67][68][69]. In our study, sacral agenesis (SA) was higher in males than females.…”
Section: Discussionmentioning
confidence: 54%
“…The total absence (agenesis) of the sacral canal of the dorsal wall among the Bangladeshi population was 5.0%. Multiple studies revealed that the incidence of complete agenesis of the dorsal wall in the sacrum varies from 2.58% to 20% (Table 2) [10,30,59,[62][63][64][65][66][67][68][69]. In our study, sacral agenesis (SA) was higher in males than females.…”
Section: Discussionmentioning
confidence: 54%